Assessing Banks Managerial Efficiency during the Covid-19 Pandemic: Evidence from Selected Nigerian Banks - Akobundu, Eleazar Goddey; Oboreh, Justina; Jeroh, Edirin (International Journal of Management and Sustainability, 2021)
This study analyzes the effects of COVID-19 on the managerial efficiency of commercial banks in Nigeria by analyzing secondary data relating to five (5) sampled commercial banks, the stocks of which are currently traded on the country’s equity market. The five banks were purposely selected, and the secondary data obtained were analyzed using descriptive and diagnostic tests, along with the structural equation model and regression technique. The results of this analysis indicate that the outbreak of COVID-19 significantly influenced the managerial efficiency of the five banks studied here. Given this result, we recommend that banks should continually develop and improve on the level of e-channel penetration by customers, as this will largely keep banking transactions from being disrupted by shocks – whether external or internal. Also, the country’s apex bank and other regulatory bodies should ensure that the peculiarities of Nigeria’s economy and markets are clearly understood, so that the design and implementation of policies and strategies meant to cushion the effects of perceived external threats (such as a pandemic) on banks and the economy as a whole will be purposeful and effective.